Health Capacity to Work among Older Adults in Viet Nam - LONG THANH GIANG; AIKO KIKKAWA; DONGHYUN PARK (Asian Development Review, 2024)
In this paper, we estimated the additional health capacities to work of older Vietnamese adults by applying the Milligan–Wise and Cutler–Meara–Richards-Shubik methods with various nationally representative datasets. In following these methods, we postulated that older adults’ mortality rates, life expectancies, and health statuses were comparable to their younger counterparts. We found that there were significant differences in employment rates between various groups of older male and female adults, in which women generally had higher capacities to work than men if they both had similar mortality rates. Along with other sociodemographic and economic factors, health status is a significant factor in determining the probability of being employed for older adults. Based on these findings, we discuss needed policy options, with a focus on health-related issues, for Viet Nam to unleash the potential work capacities of older adults.